Snapshots of Coastal Ecology Using Multiproxy Analysis Reveals Insights Into the Preservation of Swamp and Marsh Environments Since the Late Pleistocene - Kendall Fontenot; Kristine L. DeLong; Brian A. Schubert; Sophie Warny; Davin J. Wallace; Carrie M. Miller; Erin Culver‐Miller; Michael J. Polito; Carl A. Reese; Kathryn Garretson; Kehui Xu; Grant L. Harley; et al. (Geochemistry, Geophysics, Geosystems, 2024)
Abstract The southeastern United States Coastal Plain ecosystem contains baldcypress (Taxodium distichum) swamps and grass‐dominated marshes. These ecosystems also occurred on the exposed continental shelf during lower sea levels but are rarely preserved due to the mechanically erosive nature of transgression and regression. Two presently marine sites on the northeastern Gulf of Mexico's continental shelf contain well‐preserved woody terrestrial sediments that were the subject of previous studies. This study continues the investigation using geochemical (δ13C, δ15N, δ34S) and palynological characteristics of these formerly terrestrial sediments to determine if swamps and/or marshes existed at the time of deposition. The first site is located ∼20 km southeast of Horn Island, Mississippi (MS) and the core has terrestrial sediments radiocarbon dated to 11,066–10,228 (2σ) calibrated years BP (early Holocene). The second site is the “Alabama Underwater Forest” located ∼13 km south of Gulf Shores, Alabama (AL) and the cores have terrestrial sediments optically stimulated luminescence dated to 63 ka (±10 ka, 2σ) to 72 ka (±16 ka, 2σ) (late Pleistocene). Geochemical results for the MS sediments indicate a swamp‐to‐freshwater marsh transitional series, whereas the AL sediments indicate a swamp‐to‐saltwater marsh transitional series, both supported by palynological results. Further exploration of the geochemical results using linear discriminant analysis, trained with published geochemical data, supports the swamp and marsh interpretations. We conclude that the near‐pristine preservation of these woody deposits is not solely due to physical mechanisms, such as rapid burial, but is also coupled with anoxia‐ and euxinia‐driven biogeochemical reactions promoting wood and woody debris preservation in swamp and marsh environments.